Association of AVPR1A gene microsatellites with Autism Spectrum Disorder in south Indian population - Mandamkulathil, Dhanesh; Pillai, Anitha Ayyappan; Poovathina, Suresh A; Chengappa, Shyamala K; Chandrasekar, Adimoolam; Murthy, Ashitha Sidappa Niranjana; Srividhya, Dhurbagula; Tirumalaraj, Sridevi; Pengaluru, Pardhanandana Reddy (International Journal of Scientific Research in Biological Sciences, 2019)
Pharmacological studies have shown the therapeutic potential of Arginine Vasopressin Receptor (AVPR1A) for Autism Spectrum Disorders (ASDs) with socialization and communication symptoms. Present study investigated the association of promoter microsatellites (RS1 and RS3) polymorphisms of AVPR1A gene with ASDs in south Indian ethnicity. We recruited 225 subjects that constitutes of 118 ASD subjects diagnosed based on DSM-IV criteria and 107 controls, aged between 2 and 25 years of south Indian ethnicity. Case control association with RS1 allele length- 318bp, (P = 0.009); allele length- 330bp (P = 0.02); overall association with RS1 (P = 0.02) and RS3 allele length- 333bp (P = 0.002) , 335bp (P = 0.045) over all association (P = 0.002) with ASDs was found to be significant. Our results reveal that, RS1 and RS3 microsatellites of AVPR1A gene contribute to the susceptibility of ASD in south Indian ethnicity.